Pengaruh Konseling dengan Pemberian Buku Saku terhadap Penggunaan Metode Kontrasepsi Jangka Panjang di Wilayah Puskesmas Tikung Kecamatan TikungKabupaten Lamongan: The Effect of Counseling by Providing Pocket Books on the Use of Long-Term Contraception Methods in the Tikung Health Center Area, Tikung District, Lamongan Regency - Titin Irawati (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Indonesia is a country with the Fourth largest population in the world. The coverage of the LongTerm Contraceptive Method (MKJP) at the Tikung Health Center is very low, at 8.3%. According to previous research, pocket books effectively improve knowledge. The purpose of this study was to determine the effect of pocket book counseling on the use of MKJP. This research is an experimental study with a post test control group design. The sample in this study were couples of childbearing age who met the criteria that had been set. The sampling technique was purposive sampling. The sample size was calculated using the formula for the difference in the average of the two samples and obtained each experimental and control group, namely 60 respondents. The experimental group was given counseling with a pocket book and the control group was given counseling with a leaflet. Data analysis used univariate, bivariate with Wilcoxon test and Mann Whitney test and multivariate with logistic regression test. Based on the Mc Whitney test, it was found that the p value < 0.05 that the provision of pocket books was more effective than the provision of leaflets in the use of MKJP.